ANALISIS PENYAJIAN LAPORAN KEUANGAN BERDASARKAN SAK-ETAP PADA KPN SERUMPUN DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN REJANG LEBONG - Yunus Dwikasmanto (Politeknik Raflesia Press, 2021)
Financial statements are a means of communicating financial information from the results of the accounting activity process that can assist users of financial statements in making decisions. Generally accepted Financial Accounting Standards are considered complicated to apply to business entities that do not have public accountability. Based on this, IAI issued Financial Accounting Standards for Entities Without Public Accountability (SAK-ETAP) which can accommodate accounting needs for entities that do not have public accountability. This study aims to analyze the application of SAK-ETAP in the presentation of the financial statements of the Cognate KPN of the Education and Culture Office of Rejang Lebong Regency. KPN Cognate of the Education and Culture Office of Rejang Lebong Regency is a business entity that manages members' funds in the form of savings and loans. The method used in this research is comparative descriptive analysis. The results of the study based on the presentation of the balance sheet, income statement, statement of changes in equity, and cash flow statements for 2019, show that the KPN Cognate of the Education and Culture Office of Rejang Lebong Regency has not presented notes on financial statements (CALK), there is an error in the classification of account posts, and there are inconsistencies in updating the statement of cash flows. This study suggests that cooperatives disclose cooperative accounting policies in CALK, update each component of financial statements, and hire employees who are skilled in accounting.